Pemodelan Enterprise Resource Planning Untuk Meningkatkan Efisiensi Kinerja Pada PT Karya Perdana Baru - Ivan Wiranata William (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2020)
The research method used is a qualitative method. The stages of the qualitative method is to plan, gather information on problems that occur with interviews conducted six times (to the director and division). After that it starts with the analysis method used is a balanced scorecard, value chain and to measure performance and activities that occur in the company and Fishbone analysis to identify possibilities. This study aims to carry out an ERP approach to business processes so that ERP becomes a means to help companies to maximize company performance that can help manage companies to achieve goals. The result of this research is to prototype an ERP approach to manage the Project properly related to material planning, distribution order process (time to do distribution, lead time).